Open season [videorecording (DVD)] - Allers, Roger; Culton, Jill; Stacchi, Anthony; Kutcher, Ashton, 1978-; Favreau, Jon; Sinise, Gary (Sony Pictures Home Entertainment, 2007)
A performing grizzly bear named Boog, who has been domesticated by a park ranger, Beth, helps deer friend Elliot escape from the mullet-sporting hunter, Shaw. When the two animals escape to the forest they become lost - just as hunting season begins. To make the situation worse, Boog doesn't know how to survive outside of his beloved ranch. Elliott and Boog develop a strong bond not only between themselves but also with the other wild animals as they attempt to drive the hunters out of the forest.